Keep Track (Tenant Management System) - et. al., Lakshay Chauhan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we tend to formulate a tenant management downside.This is aimed toward developing an internet tenant management system that’s of importance to either landholder or to tenants. The Tenant Management System (TMS) may be a on-line based mostly net applications which will be accessed by any landholder or tenants happiness to specific landholder. Our aim is to produce several facilities to each landholder and tenant to manage all the small print and monetary management is additionally taken care by the appliance. Managing all the recordsof tenants may be a major issue for landholder. Thus This application provides numerous options like notification and email support, simple to manage information of tenant making dues of tenant, no paper work needed, simple retrieval of records, accessible anyplace, etc. to induce data regarding however rental homes ar presently being managed, I Prepared questionnaires and submitted them to variety of rental house managers and from the knowledge I gathered I spotted all work was done manually with tons of paper work concerned. Papers will simply get broken or wander away resulting in loss of information. It’s conjointly big-ticket to stay on shopping for files to store your records. Tons of files build an area look untidy and conjointly consume tons of area. Obtaining a definite file to see information from several files becomes a tough task. Considering those facts, I made a decision to develop a rental house management system which will solve all the issues fully fledged with this manual system. The system was developed in such manner that it provides most user friendly interface. Once you the user logs within the system mechanically show 3 types: homes form, rent payment type and tenants‟ registration type. Every type has many command buttons; new, save, cancel, delete, next, previous and exit. With the command buttons you’ll be able to manipulate the information. If you would like to feature information to the information all you would like to try to to is to click on new then {input information|input file|computer file} within the textboxes provided then click save and therefore the data can mechanically be saved. If you would like to look at information within the information you only click next or previous and therefore the information are going to be displayed for you. Once you click delete you’ll be able to delete a record that you just want. You will enter information then attempt to cancel it, it’s easy click on cancel and it’ll be canceled. For manager baby-faced with management difficulties here may be a good answer for you. The rental house management system is formed for you.